Hubungan Dukungan Sosial Orangtua dengan Resiliensi Akademik Siswa SMA - Firman, Firman; Asevdha, Viory (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Low academic resilience is one of the factors influenced by parental social support. The aim of this study is to describe: (1) students' resilience in learning, (2) parental social support for students in learning, and (3) the relationship between parental social support and students' resilience in learning. This research was conducted using a quantitative method with a correlational research design. The results of the study showed that: (1) parental social support at SMA Negeri 13 Padang was generally in the high category, with 82 students (35.34%), (2) academic resilience at SMA Negeri 13 Padang was generally in the moderate category, with 125 students (53.9%), and (3) there was a significant positive relationship between parental social support and students' academic resilience at SMA Negeri 13 Padang, with a correlation coefficient of 0.376 and a significance level of 0.000. Based on these findings, guidance and counseling services that can be provided to enhance parental social support and academic resilience among students include informational services, group counseling services, and group guidance services.